Cameroon's agrarian political economy: impact of the state's free market agrarian system reforms on coffee cooperatives' activities and market orientation. - Ngam, Ronald, Nkwain (My University, 2018)
Cameroon’s modern economy developed around a satellite-metropolis plantation dynamic within which successive European colonial masters and later, African-led governments, promoted monocrop commodity production along coastal areas for the benefit of Europe. The federating organisations employed to structure production were a combination of plantations, agriculture development zones and especially cooperatives. The period of government-controlled cooperatives was characterised by a too-big-to-fail approach; the State intervened directly in cooperatives’ affairs and managed their cashflow through the National Produce Marketing Board. Following a structural adjustment plan in the 1990s, the Cameroon State divested its interest in cooperatives and transitioned the agrarian system into a borderless, global market within a neoliberal competition state dynamic. This study investigated the impact of the Cameroonian State’s post-structural adjustment neoliberal agrarian system reforms on coffee cooperatives’ activities and market orientation. This was done through the prism of the two biggest coffee cooperatives in Cameroon, i.e. the Central Union of Agricultural Cooperatives of the West (UCCAO) and the North West Cooperative Association (NWCA). The study employed an interpretivist approach, and the extended case methodology was used to gather data. Data gathering instruments included interviews, questionnaires, participant observation, archival material and photos. Respondents were top managers of both cooperatives plus forty coffee growers. The study revealed three key findings. Firstly, the Cameroon State’s support to coffee cooperatives in the free market era is characterised by a preponderance of disparate programmes which appear to be done more for optics rather than actually providing the robust support that is needed to help producer organisations succeed. Some development experts (Chang, 2001; Gereffi, 1995; Stiglitz, 2008) are unanimous that in underdeveloped countries with threadbare infrastructure, the state has a key role to play in providing the infrastructure, communications networks, access to finance and other support necessary to develop efficient value chains that can take commodities to world markets on a consistent and reliable basis. Secondly, Cameroon’s coffee Cooperatives have made only timid and insufficient efforts to adjust to the deeply globalised free market context into which they were suddenly ushered in the 1990s after a half a century of operating as quasi parastatals. Their market orientation shows a business-as-usual approach which is ultimately self-defeating as it stops them from leveraging the opportunities offered by free market globalism. Thirdly, conclusive data from around the world reveals that the more successful modern-day cooperatives are those ones that locate themselves in parallel cooperative market economies based on solidarity, democracy and cooperation among cooperatives rather than in traditional capitalistic value chains (Wright, 2011). It is this pathway that Cameroonian cooperatives need to follow if they wish to succeed in the age of globalism.
A thesis submitted to the Faculty of Humanities, School of Social Sciences (Development Studies Programme), University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2018.
Keywords: International economic relations; Economics; Free enterprise